Comparative Efficiency Analysis of Broiler Farming Under Aftab Bahumukhi Farm Limited Supervision and Farmers Own Management - Akhter, S; Rashid, MHA (Progressive Agriculture, 2013)
This study was conducted to assess the comparative efficiency of Aftab Bahumukhi Farm Limited (ABFL) supervised broiler farms and farmers own managed broiler farms. Data were collected from randomly selected 90 broiler farmers of which 45 were ABFL supervised farmers and 45 were own managed farmers. Cobb-Douglas stochastic production function and cost frontier function were applied to determine the technical, allocative and economic efficiency of broiler farming. Technical and economic inefficiency effect models were also estimated. The estimated mean technical efficiency of all farms was 94.06 percent. Whereas it was 94.49 percent for ABFL supervised farmers and 93.66 percent for the own managed broiler farm owners. The estimated mean allocative efficiency was 96.76 percent for all farmers, and 96.51 for ABFL supervised farmers and 96.45 percent for own managed broiler farm owners. The mean economic efficiency was estimated at about 91.60 percent for ABFL supervised farmers, 90.34 percent for own managed farmers and 91.00 percent for all farmers. This implies that the cost of broiler production per farm can be reduced by 9 percent keeping the output constant. The findings reveal that ABFL supervised farmers and own managed farmers were not significantly different in terms of efficiency. DOI: http://dx.doi.org/10.3329/pa.v19i2.16962 Progress. Agric. 19(2): 195 - 204, 2008